The influence of the autochthonous wastewater microbiota and gene host on the fate of invasive antibiotic resistance genes - Narciso-da-Rocha, Carlos (2017)
The aim of this study was to assess the fate of invasive antibiotic resistance genes (ARG) discharged in wastewater. With this objective, antibiotic resistant bacteria (ARB) known to harbor specific ARG were inoculated in wastewater (hospital effluent, or municipal raw and treated wastewater) and in ultra-pure sterile water microcosms. Two sets of wastewater ARB isolates were used - set 1, Enterococcus faecalis, Acinetobacter johnsonii, Klebsiella pneumoniae and set 2, Enterococcus faecium, Acinetobacter johnsonii, Escherichia coli. Non-inoculated controls were run in parallel. Samples were collected at the beginning and at the end (15 days) of the incubation period and the abundance of the genes 16S rRNA, intI1, blaTEM and vanA and the bacterial community composition were analyzed. In general, the genes blaTEM and vanA had lower persistence in wastewater and in ultra-pure water than the genes 16S rRNA or the class 1 integron integrase intI1. This effect was more pronounced in wastewater than in ultra-pure water, evidencing the importance of the autochthonous microbiota on the elimination of invasive ARG. Wastewater autochthonous bacterial groups most correlated with variations of the genes intI1, blaTEM and vanA were members of the classes Gammaproteobacteria, Bacilli or Bacteroidia. For blaTEM, but not for vanA, the species of the ARB host was important to determine its fate. These are novel findings on the ecology of ARB in wastewater environments.